(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2025)
This study offers a comprehensive analysis of the public servant in Iraq, addressing their legal definition, relationship with the state, and the regulatory framework of their legal status. It explores career movements including promotion, transfer, secondment, and deputation, with a focus on the legal and administrative conditions governing such processes. The research also examines obstacles to promotion and related exceptions, highlighting the legal safeguards available to public employees. Drawing on Iraqi and comparative legislation, the study provides practical recommendations to enhance public service efficiency and uphold administrative justice.